Potensi Urban Farming di Kawasan Tepian Sungai Kota Palangka Raya - Hamidah, Noor; Syahrozi, Syahrozi; Nindito, Dwi Anung; Santoso, Mahdi; Kudadiri, Puput Khairani; Sulistiawati, Putri; Hasanah, Siti Fadillah; Zaini, Akhmad; Rusanisari, Anna (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Food security starts from availability on a small scale, namely households. Utilizing the function of the yard as a medium used by the community to grow their daily needs of vegetables. Urban farming as a strategic concept in meeting household needs and food security for village communities. Urban farming is an implementation of the Community Empowerment Assistant Lecturer Program of the Faculty of Engineering of Palangka Raya University in partnership with the Religious Women of RW 02/RW 03, Pahandut Seberang Subdistrict. Urban farming is located in a residential area on the banks of the Pahandut Seberang River, Pahandut District, Palangka Raya City. The service aims to stimulate riverside communities to use the area in their yards to grow vegetables as a pilot project carried out in the courtyard of the Daruth Tayyibah Mosque. The method uses qualitative methods from the results of interviews with residents' needs and consultations with residents. The result of the service was the implementation of urban farming in the courtyard of the Daruth Tayyibah Mosque, Pahandut Seberang Subdistrict, from the initial stage, discussion activities were carried out with the Head of RT.03/RW. 02 and the community, conducting outreach to the women of Koran regarding the introduction of hydroponics through, and it is hoped that the results of the urban farming pilot project can be used by women in their home gardens to grow vegetables for daily needs, and in the long term as a business opportunity for riverside communities.